Identification of a Novel Gnao-Mediated Alternate Olfactory Signaling Pathway in Murine OSNs - Scholz, Paul; Mohrhardt, Julia; Jansen, Fabian; Kalbe, Benjamin; Haering, Claudia; Klasen, Katharina; Hatt, Hanns; Osterloh, Sabrina (Frontiers in Cellular Neuroscience, 2016)
It is generally agreed that in olfactory sensory neurons (OSNs), the binding of odorant molecules to their specific olfactory receptor (OR) triggers a cAMP-dependent signaling cascade, activating cyclic-nucleotide gated (CNG) channels. However, considerable controversy dating back more than 20 years has surrounded the question of whether alternate signaling plays a role in mammalian olfactory transduction. In this study, we demonstrate a specific alternate signaling pathway in Olfr73-expressing OSNs. Methylisoeugenol (MIEG) and at least one other known weak Olfr73 agonist (Raspberry Ketone) trigger a signaling cascade independent from the canonical pathway, leading to the depolarization of the cell. Interestingly, this pathway is mediated by Gnao activation, leading to Cl- efflux; however, the activation of adenylyl cyclase III (ACIII), the recruitment of Ca2+ from extra-or intracellular stores, and phosphatidylinositol 3-kinase-dependent signaling (PI signaling) are not involved. Furthermore, we demonstrated that our newly identified pathway coexists with the canonical olfactory cAMP pathway in the same OSN and can be triggered by the same OR in a ligand-selective manner. We suggest that this pathway might reflect a mechanism for odor recognition predominantly used in early developmental stages before olfactory cAMP signaling is fully developed. Taken together, our findings support the existence of at least one odor-induced alternate signal transduction pathway in native OSNs mediated by Olfr73 in a ligand-selective manner.